Hubungan Jumlah Monosit Dan Nilai Laju Endap Darah (LED) Terhadap Lama Pengobatan Pasien Tuberculosis : Correlation Of Monocyte Number And Erythrocyte Sedimentation Rate (Esr) Value Against To Duration Of Treatment In Tuberculosis Patients - Kadarwati, Ari; Sukeksi, Andri; Putri, Gela Setya Ayu (Borneo Journal of Medical Laboratory Technology, 2023)
Tuberculosis (TBC) is a bacterial infection caused by Mycobacterium tuberculosis. The duration of TBC treatment is routinely 6 months; otherwise, resistance will develop. TBC can increase leukocytes, including monocytosis as an inflammatory response and an elevated ESR. The aim of this study was to determine the relationship between the number of monocytes and the ESR value on the duration of tuberculosis treatment in patients at the Respira Lung Hospital, Yogyakarta City. The study was conducted in June and July 2023 at the Respira Pulmonary Hospital in Yogyakarta City. The study sample was 32 tuberculosis patients and blood was drawn to determine the monocyte number and ESR value. The results showed that the average number of monocytes was 7% (normal), the ESR value was 41.59 mm/hour (high) with the average duration of tuberculosis treatment for respondents was 3 months. Spearman test obtained Sig p<0.05. This study concluded that there is a correlation between the number of monocytes and the ESR value on the duration of TB treatment in patients at the Respira Lung Hospital in Yogyakarta City, with the direction of the relationship reversed.